2014
DOI: 10.1111/mpp.12089
|View full text |Cite
|
Sign up to set email alerts
|

The target gene of tae‐miR164, a novel NAC transcription factor from the NAM subfamily, negatively regulates resistance of wheat to stripe rust

Abstract: microRNA (miRNA) participates in various physiological and biochemical processes in plants by regulating corresponding target genes. NAC [NAM (no apical meristem), ATAF (Arabidopsis transcription activation factor) and CUC (cup-shaped cotyledon)] transcription factors, usually as the targets of miR164, play important roles in the regulation of plant development and responses to abiotic and biotic stresses. In a previous study, the target gene of tae-miR164 in wheat was sequenced through degradome sequencing. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 56 publications
3
84
0
Order By: Relevance
“…Lateral root development also is influenced by the miR164-NAC1 pathway (Guo et al, 2005), and miR164 negatively regulates pathogen-induced and age-dependent cell death by target NAC4 (Lee et al, 2017) and ORE1/NAC2 (Kim et al, 2009), respectively. Similar functions of miR164 and its effect on NAC transcription factors also have been reported in rice (drought resistance; Fang et al, 2014), wheat (resistance to stripe rust; Feng et al, 2014) and Medicago truncatula (root; D'Haeseleer et al, 2011). Similar functions of miR164 and its effect on NAC transcription factors also have been reported in rice (drought resistance; Fang et al, 2014), wheat (resistance to stripe rust; Feng et al, 2014) and Medicago truncatula (root; D'Haeseleer et al, 2011).…”
Section: Discussionsupporting
confidence: 67%
“…Lateral root development also is influenced by the miR164-NAC1 pathway (Guo et al, 2005), and miR164 negatively regulates pathogen-induced and age-dependent cell death by target NAC4 (Lee et al, 2017) and ORE1/NAC2 (Kim et al, 2009), respectively. Similar functions of miR164 and its effect on NAC transcription factors also have been reported in rice (drought resistance; Fang et al, 2014), wheat (resistance to stripe rust; Feng et al, 2014) and Medicago truncatula (root; D'Haeseleer et al, 2011). Similar functions of miR164 and its effect on NAC transcription factors also have been reported in rice (drought resistance; Fang et al, 2014), wheat (resistance to stripe rust; Feng et al, 2014) and Medicago truncatula (root; D'Haeseleer et al, 2011).…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, ONAC60 is targeted by miR164 in rice (Wu et al 2009b). Additionally, a recent study from Feng and colleagues showed miR164 regulation of TaNAC21/22 gene under infection by wheat stripe rust (Feng et al 2014). This study supports a NAC/miRNA association under stress in a member of the Triticeae .…”
Section: Mirna and Stress Regulation Mechanismsmentioning
confidence: 99%
“…A number of miRNA families have now been identified in wheat, and about twenty miRNA families are conserved in diverse plant species (Yao et al, 2007;Feng et al, 2014;Han et al, 2014;Kumar et al, 2014;Sun et al, 2014). Of these, miR408 contains 21 nucleotides and has been annotated in more than 30 plant species to date, indicating a high level of conservation in different plant species (Axtell and Bowman, 2008;Kozomara and Griffiths-Jones, 2011).…”
mentioning
confidence: 99%